The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15540/nr.2.4.158
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome, Gut-Brain-Axis, and Implications for Brain Health

Abstract: As Antonio Damasio highlighted back in 1994, Descartes' division of mind and body slowed the full realization of the connectedness of the brain and the body by centuries. The simple fact that homeostasis in the brain was fully interconnected with the body has eluded researchers and clinicians even after the connection was well established. Recent studies reporting the central role in dysfunction of mental systems as a result of inflammation in the gut and the autonomic nervous system (ANS) was yet one more rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Additionally, these aromatic amines can directly enter the brain when liver function is impaired, and generate pseudo-neurotransmitters including phenylethanolamine and β-hydroxytyramine. These pseudo-neurotransmitters cannot transmit nerve impulses [ 49 , 50 ] and, therefore, may cause brain dysfunction and liver coma. Research on the influence of gut microbiota-derived metabolites on the pathophysiological mechanisms of HE found that hyperammonemia plays an important role in the progression of HE.…”
Section: Bioactive Molecules As Mediators Of the Microbiome-gut-liver...mentioning
confidence: 99%
“…Additionally, these aromatic amines can directly enter the brain when liver function is impaired, and generate pseudo-neurotransmitters including phenylethanolamine and β-hydroxytyramine. These pseudo-neurotransmitters cannot transmit nerve impulses [ 49 , 50 ] and, therefore, may cause brain dysfunction and liver coma. Research on the influence of gut microbiota-derived metabolites on the pathophysiological mechanisms of HE found that hyperammonemia plays an important role in the progression of HE.…”
Section: Bioactive Molecules As Mediators Of the Microbiome-gut-liver...mentioning
confidence: 99%
“…It has been shown to have positive effects on conditions such as depression, schizophrenia, addiction, and various neurological diseases (22). Stress and anxiety in rats have been observed to alter the composition of intestinal microbiota and decrease the production of neurogenesis factors derived from the brain (23).…”
Section: Microbiota and Neurotransmittersmentioning
confidence: 99%
“…The intestinal microbiota also has the ability to regulate hormone release through the hypothalamus-pituitary-adrenal axis, which is involved in the body's response to stress. Additionally, corticosteroid hormones released by the hypothalamus-pituitary-adrenal axis can influence the composition of the intestinal microbiota (24). The colonization of Bifidobacterium infantis in the gut has been shown to improve behavioral and stress-related brain deficits.…”
Section: Microbiota and Neurotransmittersmentioning
confidence: 99%
“…However, with populations, that have established a stable homeostatic symbiosis with beneficial microbiome, now eating foods that challenge the established microbiome, are creating new gut microenvironments for new microbiome populations that might not be compatible for normal tissue health [82][83][84][85]. The consequences of these new microbiome secreted toxins might have all kinds of health effects along the gut/brain axis [86]. With the trillions of various populations of microbes in the gut, confronting all kinds of foods, grown and processed differently, together with medications, pollutants and supplements, it seems that the chemical sequelae of the signaling from this metabolism on the physiological responses of all the organs affected would be unpredictable.…”
Section: The Role Of Epigenetics In Food Safetymentioning
confidence: 99%